SENAM KAKI DIABETES BERPENGARUH TERHADAP KADAR GULA DARAH PADA PASIEN DIABETES MELITUS TIPE I I - Meyko, Lalu Agit; Sumartini, Ni Putu; Cembun (Politeknik Kesehatan Kemenkes Sorong, 2022)
Diabetes Millitus is a disease when glucose levels in the blood are high because of the body cannot release or use insulin adequately. Foot gymnastics is exercise carried out by patients with DM to prevent injuries and help facilitate blood circulation in the legs. The aim of this study was to know the effect of Diabetes foot gymnastics on changes in blood sugar level in patients with DM Type 2 in Puskesmas Muncan District Kopang Central Lombok. The method of this study was Pre-experimental with pre-posttest design one group pretest-posttest design. The sample in this study amounted to 25 respondents of DM type 2. Sampling by purposive sampling with data collection techniques using blood sugar gauges,observation sheets, and questionnaires. Data analysis techniques using Paired sample t-test. The result of this study was there was a decrease in blood sugar levels in patients with DM type 2 after diabetes foot gymnastics with statistical test results showing a value of ρ value = 0.000 < α = 0.05 which means H0 is rejected and Ha is accepted. Conclusion:There is an influence of diabetic foot gymnastics on changes in blood sugar levels in patients with type 2 DM in the Working Area of Puskesmas Muncan Year 2021.